Effectiveness Of MSME Tax Implementation, Tax Fairness, and Tax Socialization on Tax Compliance (Empirical Study: Kediri) - Anwar, Muhkamat; Tsaqif Suwailim, Ghozy; Nur Azizia , Fatima; Purnomo, Eko (Politeknik Keuangan Negara STAN, 2024)
This study aims to determine the level of efficiency of tax compliance for MSMEs in Kediri Regency based on tax application variables, tax fairness, and tax socialization in 2023. This research is motivated by the low tax compliance of MSMEs in Indonesia, contrary to the government's efforts to optimize MSME tax compliance, considering that MSMEs have a significant role in Indonesia’s GDP. Based on the results of research conducted, it shows that the three variables used such as the application of taxes, have a significant positive influence on tax compliance with MSMEs in Kediri Regency. In line with tax implementation, tax fairness also has a significantly positive influence on MSME tax compliance in Indonesia. Meanwhile, similar conditions on tax socialization have the same influence, which is significantly positive for MSME tax compliance in Kediri Regency.